2018
DOI: 10.3390/ijfs6030060
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research into Enterprise Bankruptcy Prediction in Selected Central and Eastern European Countries

Abstract: Abstract:In developed countries, the first studies on forecasting bankruptcy date to the early 20th century. In Central and Eastern Europe, due to, among other factors, the geopolitical situation and the introduced economic system, this issue became the subject of researcher interest only in the 1990s. Therefore, it is worthwhile to analyze whether these countries conduct bankruptcy risk assessments and what their level of advancement is. The main objective of the article is the review and assessment of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 87 publications
1
48
0
Order By: Relevance
“…-the changes concerning the corporate governance in the menace of bankruptcy, -the costs of bankruptcy, -the prices of shares and the long-term results, -the changes in the legal regulations concerning bankruptcy. Many of the research studies were focused on the forecast of the bankruptcy of enterprises (Altman & Hotchkiss, 2006;Prusak, 2018;Durica et al, 2019aDurica et al, , 2019bKliestik et al, 2018).…”
Section: The Overview Of the Literaturementioning
confidence: 99%
“…-the changes concerning the corporate governance in the menace of bankruptcy, -the costs of bankruptcy, -the prices of shares and the long-term results, -the changes in the legal regulations concerning bankruptcy. Many of the research studies were focused on the forecast of the bankruptcy of enterprises (Altman & Hotchkiss, 2006;Prusak, 2018;Durica et al, 2019aDurica et al, , 2019bKliestik et al, 2018).…”
Section: The Overview Of the Literaturementioning
confidence: 99%
“…During past decades, some literature has reviewed corporate failure forecasting in detail, such as Sun et al [5], Alaka et al [20], Prusak [32], etc. Here, we briefly review more recent literature of corporate failure forecasting (shown as Table A1) and summarize the recent development as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To achieve a better forecasting performance, integrated models, which employ individual models as basis classifiers, have become a new exploring trend. A great deal of literature has demonstrated how to integrate basis classifiers for corporate failure forecasting [5,32]. To date, integrated models can be divided into two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This different approach used by SMEs causes the popularity of basic statistical techniques to remain unchanged in daily practice and a number of scientific papers can be found as well. Prusak (2018) or Klieštik et al (2018) provide an overview of the research conducted in selected central and eastern European countries. Research carried out in the area of the Czech Republic involves the works by Karas and Režňáková (2013), Klečka and Scholleová (2010), Čámská (2015, 2016), Machek (2014), and Pitrová (2011).…”
Section: Introductionmentioning
confidence: 99%